PERAN CINTA MEREK DALAM MEMEDIASI KESELARASAN GAYA HIDUP, LOYALITAS MEREK DAN WORD OF MOUTH PADA PRODUK H&M - Parida, Heni; Nurhadi, Mochamad; Ilfitriah, Aniek Maschudah; Widyantoro, Harry (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.02.TAHUN.2023DO - 10.24843/EEB.2023.v12.i02.p02, 2023)
The purpose of this study was to analyze the influence of lifestyle harmony, on brand love, brand loyalty, and word of mouth on H&M brand consumers in the Surabaya region. This research uses a type of quantitative research using primary data whose results are obtained from the questionnaire answers given to the respondents. Sample determination in this study used purposive sampling techniques with a total of 165 respondents. The variable analysis technique in this study is to use PLS-SEM. The results showed that lifestyle alignment with the brand love of H&M brand customers has a positive and significant influence. Brand love has a positive and significant effect on the brand loyalty of H&M brand customers. Brand love for the word of mouth of H&M brand customers shows a positive and significant influence. In addition, in this research there is also a role in the medical role of brand love on the relationship of lifestyle harmony and brand loyalty as well as the mediating role of brand love to the relationship of lifestyle congruence with word of mouth.